The taste of pickled bamboo shoots: Evolution of metabolites based on electronic tongue, sensory evaluation, and non-targeted metabolomics - Wei, Jinmei; Du, Jin; Li, Ke; Wang, Yuanliang; Yang, Li; Li, Zongjun (Food science & technology, 2025)
A traditional staple of fermented cuisine, pickled bamboo shoots have a distinctive flavor profile. Nevertheless, the complexities of taste modulation throughout the fermentation process have remained obscure. Decoding this information necessitates identifying key compounds and the metabolic pathways associated with taste development and formation. Phyllostachys purpurea (PP) was used as the basic substrate for the fermentation in this study. The fermentation process was subject to analysis, with a total of 17 free amino acids, 7 organic acids, and non-volatile metabolites being identified. The results showed that the untargeted metabolomic analysis yielded a total of 950 identifiable metabolites. The distinctive flavour of pickled bamboo shoots is primarily attributable to the delicate interplay of amino acids and their derivates, peptides, flavonoids, sugars, alcohols, and organic acids. Tyrosine is considered to be the precursor substance of the taste substance. Correlation analyses identified significant correlations between taste, compounds, and metabolites during the fermentation of pickled bamboo shoots. The present study has the potential to serve as a valuable reference source and to provide a theoretical foundation for the effective control and evaluation of the quality of pickled bamboo shoots. •The reduction in the bitterness of pickled bamboo shoots was linked to Lactobacillus.•Metabolic pathways regulating the quality of pickled bamboo shoots are proposed.•Taste differences and their mechanisms during fermentation of bamboo shoots were investigated.•Tyrosine is the precursor substance for sour and bitter substances.